Comparative Effects of E-Cigarette Aerosol on Periodontium of Periodontitis Patients - Xu, Fangxi; Aboseria, Eman; Janal, Malvin N.; Pushalkar, Smruti; Bederoff, Maria V.; Vasconcelos, Rebeca; Sapru, Sakshi; Paul, Bidisha; Queiroz, Erica; Makwana, Shreya; Solarewicz, Julia; Guo, Yuqi; et al. (Frontiers in Oral Health, 2021)
Introduction: Tobacco use is one of the main causes of periodontitis. E-cigarettes are gaining in popularity, and studies are needed to better understand the impact of e-cigarettes on oral health. Objective: To perform a longitudinal study to evaluate the adverse effects of e-cigarettes on periodontal health. Methods: Naïve e-cigarette users, cigarette smokers, and non-smokers were recruited using newspaper and social media. Age, gender, and ethnicity, were recorded. Participants were scheduled for two visits 6 months apart. At each visit, we collected data on the frequency and magnitude of e-cigarette and cigarette use, and alcohol consumption. Carbon monoxide levels, cotinine levels, salivary flow rate, periodontal probing depth, bleeding on probing and clinical attachment loss were also determined at both baseline and follow-up visits and compared between groups with 2-way repeated measures ANOVA. Periodontal diagnosis and other categorical variables were compared between groups with the chi-square statistic and logistic regression. Results: We screened 159 subjects and recruited 119 subjects. One-hundred-one subjects (31 cigarette smokers, 32 e-cigarette smokers, and 38 non-smokers) completed every assessment in both visits. The retention and compliance rate of subjects was 84.9%. The use of social media and craigslist was significant in recruiting e-cigarette subjects. Ethnicity and race differed between groups, as did average age in the male subjects. Carbon monoxide and salivary cotinine levels were highest among cigarette smokers. Bleeding on probing and average probing depths similarly increased over time in all three groups, but clinical attachment loss uniquely increased in e-cigarette smokers. Rates of severe periodontal disease were higher in cigarette smokers and e-cigarette users than non-smokers, but interpretation is confounded by the older age of the cigarette smokers. Conclusion: Among the recruited participants, clinical attachment loss after 6 months was significantly worse only in the e-cigarette smokers. This study design and protocol will assist in future larger studies on e-cigarette and oral health.